Climate and taxonomy underlie different elemental concentrations and stoichiometries of forest species: the optimum ``biogeochemical niche'' - Sardans, J; Penuelas, J (PLANT ECOLOGY, 2014)
We previously hypothesised the existence of a ``biogeochemical niche{''} occupied by each plant species. Different species should have a specific elemental composition, stoichiometry and allocation as a consequence of their particular metabolism, physiology and structure (morphology) linked to their optimal functioning under the environmental (abiotic and biotic) conditions where they have evolved. We tested this hypothesis using data from the Catalan Forestry Inventory that covers different forest groups growing under a large climatic gradient. Mediterranean species that occupy hotter-drier environments have lower leaf N, P and K concentrations than non-Mediterranean forest species. Within a determined climatic biome, different species competing in the same space have different elemental compositions and allocations linked to their taxonomical differences and their phenotypic plasticity. Gymnosperms have a proportionally higher elemental allocation to leaves than to wood, higher C concentrations, and lower N, P and K concentrations mainly in the stem and branches than angiosperms. The differences among species are linked to asymmetrical use of different elements, suggesting that the biogeochemical niche is a final expression and consequence of long-term species adaptation to particular abiotic factors, ecological role (stress tolerant, ruderal, competitor), different soil occupations and use of resources to avoid interspecific competition, and finally of a certain degree of flexibility to adapt to current environmental shifts.
Keywords: Biogeochemical niche; C:N; Mediterranean; N:P; Nutrients; phosphorus; Potassium

Nutrients and trace elements content of wood decay fungi isolated from oak (Quercus ilex). - Campos, Juan a (Biological trace element research, 2011)
The presence of chemical elements and the differences in their concentration in the fruiting bodies of wood decay fungi may reflect their activity either as saprobes or parasites and the intimate physiological relation with the substrate from which they extract their nutrients. In order to test this hypothesis, we carried out a systematic sampling of eight species of wood decay fungi on oak (Quercus ilex). The data show that the concentration of some elements exhibits a very wide range of values for the species tested, which could mean that the relative content of some elements may provide clues about the nature of the substrate and, moreover, about the nutritional physiology. The comparison between the foliar analysis (FA) and the elemental content of fungi may shed light on the specific physiological behaviour of the species. Potassium is an element accumulated in fungal biomass in higher quantities than in the FA. By contrast, calcium appears in foliar analysis in much higher quantities than in fungal fruiting bodies' biomass. Concerning this element, we have also found profound differences between the two species phylogenetic groups and lifestyle. Of all elements measured, we believe that the relative accumulation of K and Ca may be related to the close connection between fungi and the substrate on which they live and may also explain their physiological role as saprobes or parasites. When the lifestyle and the systematic position of the different species sampled were compared, differences also emerged in the content of Na and Ca.
The following values have no corresponding Zotero field: accession-num: 21748305
Keywords: Epiphytic fungi; Heavy metals; Nutrients; Nutrition physiology; Saprobe fungi; Trace Elements

Influence of different post-planting treatments on the development in Holm oak afforestation - Jiménez, M. N.; Fernández-Ondoño, E.; Ripoll, M. A.; Navarro, F. B.; Gallego, E.; De Simón, E.; Lallena, a. M.; Simón, E; Lallena, a. M. (Trees, 2007)
This work examines the inﬂuence of different post-planting treatments in the development of afforested Holm oak, Quercus ilex L. subsp. ballota (Desf.) Samp., in an abandoned agricultural ﬁeld in SE Spain. A total of nine post-planting treatments were carried out: tilling spring and autumn in different years, spreading of organic and inorganic mulch, irrigation in different periods. Soil preparation prior to planting consisted of digging of a hole with a backhoe excavator of 80 HP and homogenized the proﬁle characteristics. Survival, nutrient concentrations in both leaves and soil, and foliage surface have been studied. Dryseason irrigation every 2 weeks provided the best survival rate (98.3%), while mulching with solid urban wastes caused the worst results (6.6%). The supply of forest debris increased the N, K, and Mn concentrations at all depths with respect to the other treatments, and the solid urban waste had the same effect in N, P, K, Na, Cu, Fe, and Zn. All the foliar nutrients decreased in 2005 with respect to the 2004 sampling, except in N, Cu, and Zn. The use of foliar nutrient concentrations, together with the increase in leaf surface is proposed as a non-destructive index of development and of forestation stands in the ﬁrst stages of growth. The application of forest debris, and particularly the placement of boulders in the beds of individual trees proved most effective in sapling development.
Keywords: á; á semi-arid; Afforestation; afforestation á post-planting treatments; Holm oak; holm oak á nutrients; Nutrients; Post-planting treatments; semi-arid

The influence of mycorrhization with Tuber melanosporum in the afforestation of a Mediterranean site with Quercus ilex and Quercus faginea - Domínguez Núñez, José Alfonso; Serrano, Jesús Selva; Barreal, José Antonio Rodríguez; González, José Antonio Saiz De Omeñaca (Forest Ecology and Management, 2006)
A Holm oak (Quercus ilex L.) and Lusitanian oak (Quercus faginea) stand establishment, mycorrhizated with black trufﬂe (Tuber melanosporum Vitt.), situated in the north of Alicante, south-eastern Spain, was analyzed during the second year of plantation. The mycorrhization improved seedling growth, especially that of the shoots, encouraged water uptake of the seedlings during the summer drought, and improved total phosphorus absorption. Tuber melanosporum was found to colonize the roots of the seedlings very successfully
Keywords: ectomycorrhiza; Nutrients; quercus faginea lamk; Quercus ilex L; Reforestation; tuber melanosporum vitt; water stress

Influence of fire and tree-fell on physiological parameters in Quercus ilex resprouts - Fleck, I; Grau, D; Sanjosé, M; Vidal, D (Ann. For. Sci., 1996)
Variations in the physiology of two kinds of resprout (originated after fire and after tree-fell) of Quercus ilex were analyzed under field conditions and compared with respect to the original, undisturbed vegetation, located within a Mediterranean watershed (northeast Spain). Resprouting vegetation of Quercus ilex after fire or after tree-fell showed, during the next growing seasons, enhanced photosynthesis, leaf conductance and Rubisco activity with respect to the original vegetation, especially under high temperature, irradiance and vapor pressure deficit (VPD). The lack of differences in nutrient (N,C,P,K and Ca) and soluble carbohydrate concentrations in leaves of resprouts originated after fire or after tree-fell indicates the independence of nutrients released by the action of fire and the contribution of underground organs. Differences in leaf mass per area (LMA) were due to increased thickness in resprouts whereas density was the same. N investment in chlorophylls or Rubisco was not different in control or either kind of resprout. The increased amount of carotenoids in resprouts contributed to providing protection from photoinhibitory processes
Keywords: fire; Gas exchange; Nutrients; photosynthetic pigments; Quercus ilex; tree-fell

Influence of fire and tree-fell on physiological parameters in Quercus ilex resprouts - Fleck, I.; Grau, D.; Sanjose, M.; Vidal, D. (Ann. For. Sci., 1996)
Variations in the physiology of two kinds of resprout (originated after fire and after tree-fell) of Quercus ilex were analyzed under field conditions and compared with respect to the original, undisturbed vegetation, located within a Mediterranean watershed (northeast Spain). Resprouting vegetation of Quercus ilex after fire or after tree-fell showed, during the next growing seasons, enhanced photosynthesis, leaf conductance and Rubisco activity with respect to the original vegetation, especially under high temperature, irradiance and vapor pressure deficit (VPD). The lack of differences in nutrient (N,C,P,K and Ca) and soluble carbohydrate concentrations in leaves of resprouts originated after fire or after tree-fell indicates the independence of nutrients released by the action of fire and the contribution of underground organs. Differences in leaf mass per area (LMA) were due to increased thickness in resprouts whereas density was the same. N investment in chlorophylls or Rubisco was not different in control or either kind of resprout. The increased amount of carotenoids in resprouts contributed to providing protection from photoinhibitory processes
Keywords: fire; Gas exchange; Nutrients; photosynthetic pigments; Quercus ilex; tree-fell